VD_FINDINFO HC / 2012 / 301 vom 10. Mai 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC, 276 al. 1 CPC (CH)